How Vatican II influenced female enfranchisement: A story of rapid cultural change - Anna Maria Koukal (Center for Research in Economics, Management and the Arts (CREMA), 2017)
The importance of culture for human behavior is well established in the economic literature. So far, most authors have emphasized the long persistence of cultural traits. In contrast, this paper deals with an important case of a rapid update of culturally rooted beliefs and behavior. Using a newly composed historical dataset (1919-1984), this paper provides evidence that the Second Vatican Council (1962–1965) had a rapid effect on Catholics' voting behavior pertaining to female enfranchisement in Switzerland. In various difference-in-differences settings, the Second Vatican Council turns out to increase the acceptance of women's suffrage in Catholic municipalities, when compared to Protestant municipalities.
Keywords: N34; Z12; D72; 330; Catholic Church; Second Vatican Council; rapid cultural change; female enfranchisement